3PC-019 In use physicochemical and microbiological stability of diluted solutions of the monoclonal antibody nivolumab. (24th March 2020) - Rivano, M; Selmin, F; Camuffo, L; Cancanelli, L; Mangoni, G; Piccoli, MA; Longobardo, G; Cilurzo, F; Minghetti, P
Abstract : Background and importance: Nivolumab, a fully human IgG4 anti-PD-1 monoclonal antibody, is available as a concentrated solution for intravenous (IV) injection and diluted in 0.9% saline. These solutions are reported to be physically and chemically stable for 24 hours at 2–8°C and a maximum of 8 hours at 20–25°C. As the 'real world' use after dilution in IV infusion bags may exceed the manufacturer's recommendations, 'in use' studies assessing their stability is important as the formulation components are diluted and may not be able to protect the protein against degradation or denaturation. Aim and objectives: The aim of the study was to assess physicochemical and microbiological in use stability of diluted solutions of nivolumab stored at 2–8°C. Material and methods: Four polyolefin bags of nivolumab were compounded under aseptic conditions at a concentration of 2 mg/mL with 0.9% saline solution and stored at 2–8°C over a 7 day period. At selected time points, different methods were used to evaluate stability: pH, osmolality, turbidimetry, dynamic light scattering (DLS), size exclusion chromatography-high performance liquid chromatography (SEC-HPLC) and gel electrophoresis. Microbiological assays were also performed after 30 days. Results: Diluted nivolumab solutions remained clear and colourless with no visible particles during the test period. Physicochemical analyses demonstrated that all samples were not affected in terms of formation of subvisible particles or changes in pH or osmolality. Results of SEC-HPLC analyses revealed no change in high molecular weight, soluble aggregate or low molecular weight fragmented product. Moreover, the relative ratio remained constant over time. These results were also confirmed by gel electrophoresis under both no reducing and reducing conditions as no change in band distribution was detected. Finally, no bacterial or fungal contamination was observed in any of the samples tested after 30 day of storage. Conclusion and relevance: These analyses demonstrated that nivolumab under the dilution conditions required for IV infusion can be stored for 7 days at 2–8°C with no evidence of physical or chemical alteration. When further data are available on how quality and potency may vary over time under different environmental factors, these results may support the possibility of compounding 'dose banding' batches in order to improve the patient's management, pharmacy workload and reduce costs. References and/or acknowledgements: No conflict of interest.